2023
DOI: 10.17582/journal.aavs/2023/11.3.453.458
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Fermentation Products Turbinaria murayana Seaweed in Rations on the Quality of Quail Eggs (Coturnix coturnix japonica)

Abstract: This study aimed to see the effect of fermented Turbinaria murayana seaweed using Local Microorganisms (LMo) made from fruit waste in rations on the quality of quail eggs. This study used a completely randomized design of 5 treatments with four replications. The treatment gave Turbinaria murayana seaweed fermented products with different levels, namely 0, 5, 10.15, and 20% in the ration. Research data were analyzed using analysis of variance (ANOVA), and differences between treatments were tested using the Dun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
6
2
Order By: Relevance
“…This experiment's measurements of eggshell thickness, which ranged from 0.14 to 0.17 mm, are consistent with those made public by Reski et al (2023) and Kusumorini et al (2021), who found that the thickness range was 0.14 to 0.18 mm. Analysis of variance results indicated no interaction (p>0.05) between temperature and storage time on the eggshell thickness of quail eggs fed a diet containing 20% fermented T. murayana seaweed.…”
Section: Shell Thicknesssupporting
confidence: 90%
See 3 more Smart Citations
“…This experiment's measurements of eggshell thickness, which ranged from 0.14 to 0.17 mm, are consistent with those made public by Reski et al (2023) and Kusumorini et al (2021), who found that the thickness range was 0.14 to 0.18 mm. Analysis of variance results indicated no interaction (p>0.05) between temperature and storage time on the eggshell thickness of quail eggs fed a diet containing 20% fermented T. murayana seaweed.…”
Section: Shell Thicknesssupporting
confidence: 90%
“…The T. murayana seaweed comprises bioactive compounds such as alginate, fucoidan, and fucoxanthin, which have the potential to support egg quality maintenance and lower the cholesterol level within the yolk. Reski et al (2023) reported that alginate contained in T. murayana seaweed could assist in reducing the cholesterol content of quail egg yolks and preserving their quality. The mechanism for reducing egg yolk cholesterol by alginates contained in seaweed is through indigestible alginates binding bile salts in the digestive tract.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The egg weight in this study ranged between 11.15 -11.34 g/egg. This result is higher compared to the survey by Asrori (2019), who noted that the importance of quail eggs with the addition of papaya leaf flour ranged between 10.52 -10.96 g/egg and 9.42-10.33 g/egg reported by (Reski et al, 2023).…”
Section: Egg Weightcontrasting
confidence: 61%